Analysis of plausibility of distractors of pedagogical tests - Irina N. Bulanova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In article features of test tasks of the closed type are considered. The analysis of appeal of distractors of the test tasks applied to monitoring of progress of students on department of the higher mathematics and applied informatics of the Samara state technical university is carried out. The hypothesis of uniform distribution of distractors is checked.